A Comparative Analysis of Multimodal Discourse on Chinese and International Memorial Museum Official Websites: A Visual Grammar Perspective - Guo, Fei; Huang, Xuhua; Hu, Wenrui; Tong, Xin; Liang, Lingling (Journal of Humanities and Social Sciences Studies, 2025)
This study conducts a comparative multimodal discourse analysis of four official memorial museum websites from China, the United States, Australia, and New Zealand, using Kress and van Leeuwen’s visual grammar framework. Focusing on representational, interactive, and compositional meanings, the research explores how digital commemorative discourse constructs national memory, identity, and ideology. Findings reveal that each country adopts distinct multimodal strategies aligned with its cultural values and historical narratives. China emphasizes ideological symbolism and institutional authority through conceptual processes and rigid compositional framing. The U.S. employs dynamic narrative imagery and open design to reflect democratic ideals. Australia personalizes remembrance through everyday civilian imagery and emotionally resonant layouts, while New Zealand foregrounds bicultural engagement and inclusivity using symbolic Māori representations. These visual configurations not only shape how history is presented but also how audiences are positioned—whether as observers, participants, or learners. The study underscores the role of digital interfaces as active agents in shaping public memory and highlights the value of cross-cultural multimodal analysis in understanding how nations visually encode collective remembrance.This research demonstrates that national memorial museum websites are not neutral platforms but active producers of meaning. Through their visual and multimodal discourse, these sites naturalize particular histories, mediate cultural ideologies, and shape collective memory. The study contributes to expanding the scope of multimodal discourse analysis by applying visual grammar theory to digital commemorative interfaces and highlights the importance of culturally informed design in the representation of public history.